2009
DOI: 10.1002/bem.20473
|View full text |Cite
|
Sign up to set email alerts
|

Teratological evaluation of mouse fetuses exposed to a 20 kHz EMF

Abstract: As a continuation of our previous study, we performed a teratological evaluation of the importance of gestational age with regards to the exposure of 20 kHz intermediate frequency magnetic field (IF) on pregnant ICR mice. The pregnant mice were exposed to a 20 kHz IF magnetic field for 8 h/day in a carousel irradiator at 30 microT which is the limit standard for occupational population in Korea. The animals were sacrificed on the 18th day of gestation and the fetuses were examined for mortality, growth retarda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In line with our results, Ogawa et al demonstrated no significant difference of growth and external morphology and visceral and skeletal abnormalities in fetuses following exposure of pregnant rats to 1.95-GHz EMFs 90 min/ d. 18 Similarly, no observable morphological abnormalities were reported in pups exposing to 20 kHz prenatally. 19 Similar to our results, Poulletier de Gannes et al showed that repeated exposure to the 2450 MHz Wi-Fi wireless signal had no teratogenic effect on the prenatal and postnatal development. 31 In contrast, Saito et al discovered some skeletal abnormalities such as polydactyly, abdominal fissure, vestigial 13th rib, fused rib, and lumbar rib.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our results, Ogawa et al demonstrated no significant difference of growth and external morphology and visceral and skeletal abnormalities in fetuses following exposure of pregnant rats to 1.95-GHz EMFs 90 min/ d. 18 Similarly, no observable morphological abnormalities were reported in pups exposing to 20 kHz prenatally. 19 Similar to our results, Poulletier de Gannes et al showed that repeated exposure to the 2450 MHz Wi-Fi wireless signal had no teratogenic effect on the prenatal and postnatal development. 31 In contrast, Saito et al discovered some skeletal abnormalities such as polydactyly, abdominal fissure, vestigial 13th rib, fused rib, and lumbar rib.…”
Section: Discussionsupporting
confidence: 92%
“…In animal experiments, there are some studies reporting detrimental effects of gestational exposure of high magnetic fields on testis, 7,8 kidney, 9 ovary, 10 heart, 11 bone and muscle tissue 12 as well as teratogenic and behavioral effects on embryos, [13][14][15][16][17] although there are documents reporting no adverse effect of prenatal exposure of high magnetic fields on embryos. 18,19 Our surveys on available sources revealed that there is still a paucity of molecular studies regarding forelimb development following prenatal exposure of 2.4 GHz EMFs. It has been shown that the EMFs with a carrier frequency similar to that used by a microwave oven (about 2.45 GHz) may have positive effects in an exposed population.…”
Section: Introductionmentioning
confidence: 99%
“…900 MHz EMF exposure led to decrease in SOD, GSH-Px and catalase levels, and increase in MDA and NO levels in kidney tissue and in addition, increase in urine NAG levels were also noted in two different studies. 27,28 In our study, we found higher levels of TOS and MDA, lower levels of TAS and SOD levels in kidney tissue after exposure to 2.45 GHz EMF prenatally. Post-natal exposure caused higher TOS levels and lower TAS and SOD levels in kidney tissues, but differences were not statistically significant.…”
Section: Discussionsupporting
confidence: 57%
“…29 Tubular involvement was also demonstrated with two different studies by showing high levels of urine NAG levels. 27,28 Bedir et al 9 found mild pathological changes as tubular dilatation, vacuolization, epithelial desquamation, degenerations of cells, and Bowman's capsule dilatation in kidneys of prenatally 900 MHz exposed rats. A recent study that investigated the harmful effects of 900 MHz EMF is showed glomerular dilatation and damage in tubules.…”
mentioning
confidence: 99%
“…In addition, there were no statistical significant differences between the IF series and the corresponding controls for lymphoma development (Svedenstal and Holmberg 1993). Our previous experiments of 20 kHz with 6.25 mT and 30 mT and of other shaped fields MF exposure using animal fetuses exposed during pregnant period, did not induce any malformation, either (Kim et al 2004;Lee et al 2009;St-Pierre et al 2008).…”
Section: Discussionmentioning
confidence: 63%